The Influence of Price Perceptions, Promotions and Service Quality on Customer Satisfaction with Maxim Online Motorcycle Taxi Services in Depok City - Suratriadi, Panji (ProBisnis : Jurnal Manajemen, 2023)
One practical and efficient alternative is an online motorbike taxi, which can take you to your workplace or the commuter line train station faster than other public transportation. The era of using the internet to build online motorbike taxi ordering applications has changed local motorbike taxis to internet-based ones via smartphone applications. The online motorcycle taxis that dominate in this city are Gojek and Grab; apart from that, Maxim offers cheaper rates than the others. This research aims to determine the influence of price perceptions, promotions, and service quality on customer satisfaction with Maxim's online motorcycle taxi service in Depok City. This research uses a quantitative descriptive method by distributing questionnaires via Google Forms. Meanwhile, the collection methods used are observation, questionnaires, documentation, and literature. In this research, the population is all online motorcycle taxi customers in Depok City who have used the Maxim application. In the research using a sample of 120 respondents. In analyzing the research data, SPSS 25 was used to calculate the results of the Multiple Linear Regression variable test, t-test, F test, and determination analysis. The results of this research show that, based on the t-test, price perception has a positive and insignificant effect on customer satisfaction, and based on the t-test, promotion and service quality have a positive and significant effect on customer satisfaction. Based on the results of the F Test, perceptions of price, promotion and service quality together significantly affect customer satisfaction with the Maxim online motorcycle taxi service in Depok City. Based on the results of multiple regression analysis, the influence of price perceptions, promotions and service quality on customer satisfaction is only 78.5%. In comparison, the remaining 21.5% is influenced by other variables not examined in this research.